Historical blocking: CN 2023-11-12 (China) - Voidly (Voidly Global Censorship Index, 2023)
CRITICAL severity censorship detected in China. Data sourced from ooni-historical-backfill.
Censorship Incident ID: CN-2023-0538. Severity: critical. Confidence: 97%